Systematic analysis of the polyphenol metabolome using the Phenol‐Explorer database. Issue 1 (15th October 2015) - Rothwell, Joseph A.; Urpi‐Sarda, Mireia; Boto‐Ordoñez, Maria; Llorach, Rafael; Farran‐Codina, Andreu; Barupal, Dinesh Kumar; Neveu, Vanessa; Manach, Claudine; Andres‐Lacueva, Cristina; Scalbert, Augustin
Abstract : Scope: The Phenol‐Explorer web database details 383 polyphenol metabolites identified in human and animal biofluids from 221 publications. Here, we exploit these data to characterize and visualize the polyphenol metabolome, the set of all metabolites derived from phenolic food components. Methods and results: Qualitative and quantitative data on 383 polyphenol metabolites as described in 424 human and animal intervention studies were systematically analyzed. Of these metabolites, 301 were identified without prior enzymatic hydrolysis of biofluids, and included glucuronide and sulfate esters, glycosides, aglycones, and O ‐methyl ethers. Around one‐third of these compounds are also known as food constituents and corresponded to polyphenols absorbed without further metabolism. Many ring‐cleavage metabolites formed by gut microbiota were noted, mostly derived from hydroxycinnamates, flavanols, and flavonols. Median maximum plasma concentrations ( C max ) of all human metabolites were 0.09 and 0.32 μM when consumed from foods or dietary supplements, respectively. Median time to reach maximum plasma concentration in humans ( T max ) was 2.18 h. Conclusion: These data show the complexity of the polyphenol metabolome and the need to take into account biotransformations to understand in vivo bioactivities and the role of dietary polyphenols in health and disease.